Microgravity and Hypergravity Induced by Parabolic Flight Differently Affect Lumbar Spinal Stiffness - Swanenburg, Jaap; Langenfeld, Anke; Easthope, Christopher A.; Meier, Michael L.; Ullrich, Oliver; Schweinhardt, Petra (Frontiers in Physiology, 2020)
The objective of this study was to determine the response of the lumbar spinal motor control in different gravitational conditions. This was accomplished by measuring indicators of lumbar motor control, specifically lumbar spinal stiffness, activity of lumbar extensor and flexor muscles and lumbar curvature, in hypergravity and microgravity during parabolic flights. Three female and five male subjects participated in this study. The mean age was 35.5 years (standard deviation: 8.5 years). Spinal stiffness of the lumbar 3 vertebra was measured using impulse response; activity of the erector spinae, multifidi, transversus abdominis, and psoas muscles was recorded using surface electromyography; and lumbar curvature was measured using distance sensors mounted on the back-plate of a full-body harness. An effect of gravity condition on spinal stiffness, activity of all muscles assessed and lumbar curvature (p's < 0.007) was observed (Friedman tests). Post-hoc analysis showed a significant reduction in stiffness during hypergravity (p < 0.001) and an increase in stiffness during microgravity (p < 0.001). Activity in all muscles significantly increased during hypergravity (p's < 0.001). During microgravity, the multifidi (p < 0.002) and transversus abdominis (p < 0.001) increased significantly in muscle activity while the psoas (p = 0.850) and erector spinae muscles (p = 0.813) did not change. Lumbar curvature flattened in hypergravity as well as microgravity, albeit in different ways: during hypergravity, the distance to the skin decreased for the upper (p = 0.016) and the lower sensor (p = 0.036). During microgravity, the upper sensor showed a significant increase (p = 0.016), and the lower showed a decrease (p = 0.005) in distance. This study emphasizes the role of spinal motor control adaptations in changing gravity conditions. Both hypergravity and microgravity lead to changes in spinal motor control. The decrease in spinal stiffness during hypergravity is interpreted as a shift of the axial load from the spine to the pelvis and thoracic cage. In microgravity, activity of the multifidi and of the psoas muscles seems to ensure the integrity of the spine.